The Impact of Flipbook Maker Media on Learning Outcomes of Class XI High School Students in History Subjects - Apriyani Putri Rezeki; Suranto AW (STAI Hubbulwathan Duri, 2023)
This study examined the impact of incorporating Flipbook Maker as a teaching tool on history learning. The research utilized a quasi-experimental design involving a pretest-posttest control group. Purposive sampling was used to select a sample of 28 students from the eleventh grade. Research data was collected and student learning outcomes were evaluated through a multiple-choice test consisting of 20 items. To compare the experimental group, which received instruction using Flipbook Maker, with the control group, which received traditional teaching methods, the research data was analyzed using a t-paired sample test. The t-test results, with a significance level of 0.001, indicated a significant influence of Flipbook Maker on students' history learning outcomes. The analysis demonstrated that the average post-test scores of students in the experimental group (using Flipbook Maker) were significantly higher than those in the control group (utilizing traditional teaching methods). Consequently, it can be concluded that Flipbook Maker is effective in improving students' history learning outcomes. This research carries important implications for history education in schools, as Flipbook Maker can serve as an effective alternative in teaching, facilitating a better understanding of historical concepts among students. It is recommended that history teachers and educators consider integrating this tool into their curriculum and teaching strategies to enhance the quality of history education at the high school level. By doing so, they can provide students with a more engaging and interactive learning experience, leading to improved learning outcomes in history.